DAM BREAK EVENT MODELLING AND CASE STUDY: A CORRELATIONSHIP BETWEEN BREACH DISCHARGES AND DAM PHYSICAL PARAMETERS IN MALAYSIA - Heng, H.H.; Pan, W.F.; Chan, J.A. (Journal of Engineering & Technological Advances, 2025)
Dam break incident is an extreme rare event, but the impact could be potentially devastating with losses of human lives and property damages along the torrential flow path of a river basin. This paper correlates the estimated maximum dam breach discharges with the hydrological parameters such as probable maximum precipitation/flood (PMP/PMF) and other dam’s physical parameters in Malaysia. The empirical results and other associated parameters of fourteen dam break studies in Malaysia were adopted in this study. Two critical and important dam physical parameters, i.e. the height or elevation and the volume of storage behind the dam are found directly proportionate to the magnitude of discharges during dam breaching events. The aggregate product of these two physical parameters is termed as dam factor (DF). These physically based parameters were also indirectly related to the duration of the time of failure and the final breach width. A regression analysis was carried out to correlate the breach discharge and DF for various dam break studies in Malaysia. The prediction of the final breach width and time of failure could also be used as a first hand basis for other dam break study. Comparisons of dam breach discharges were also made using various selective equations empirically developed in the literature. The results were mostly consistent and agreeable to 14 dam case studies in Malaysia.